Revealing the Role of Hydrogen in Highly Efficient Ag-Substituted CZTSSe Photovoltaic Devices: Photoelectric Properties Modulation and Defect Passivation - Xiaoyue Zhao; Jingru Li; Chenyang Hu; Yafang Qi; Zhengji Zhou; Dongxing Kou; Wenhui Zhou; Shengjie Yuan; Sixin Wu (Nano-Micro Letters)
Highlights The Ag/H co-doping strategy has been proposed to promote the performance of Cu2ZnSn(S,Se)4 (CZTSSe) devices. The incorporation of H in Ag-based CZTSSe photovoltaic absorber is expected to improve the poor electrical conductivity and the low carrier density caused by Ag substitution Benefiting from the synergism of the excellent defect passivation effect and photoelectric properties complementary effect enabled by Ag/H co-doping, a champion device with 14.74% efficiency is achieved